Return Migration, Self-Selection and Entrepreneurship in Mozambique - Catia Batista; Tara McIndoe-Calder; Pedro C. Vicente (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2014)
Does return migration affect entrepreneurship? This question has important implications for the debate on the economic development effects of migration for origin countries. The existing literature has, however, not addressed how the estimation of the impact of return migration on entrepreneurship is affected by double unobservable migrant self-selection, both at the initial outward migration and at the final inward return migration stages. This paper uses a representative household survey conducted in Mozambique in order to address this research question. We exploit variation provided by displacement caused by civil war in Mozambique, as well as social unrest and other shocks in migrant destination countries. The results lend support to negative unobservable self-selection at both and each of the initial and return stages of migration, which results in an under-estimation of the effects of return migration on entrepreneurial outcomes when using a 'naive' estimator not controlling for self-selection. Indeed,'naive' estimates point to a 13 pp increase in the probability of owning a business when there is a return migrant in the household relative to non-migrants only, whereas excluding the double effect of unobservable self-selection, this effect becomes significantly larger - between 24 pp and 29 pp, depending on the method of estimation and source of variation used.
Keywords: F22; L26; O15; 330; international migration; return migration; entrepreneurship; selfselection; business ownership; migration effects in origin countries; household survey; Mozambique; sub-Saharan Africa